Activity Enhancement of Tetrahexahedral Pd Nanocrystals by Bi Decoration towards Ethanol Electrooxidation in Alkaline Media. (20th April 2015) - Wang, Ping; Lin, Xiao; Yang, Bo; Jin, Jia-Mei; Hardacre, Christopher; Yu, Neng-Fei; Sun, Shi-Gang; Lin, Wen-Feng
Graphical abstract: Highlights: Tetrahexahedral Pd nanocrystals (THH Pd NCs) without and with Bi decoration were prepared Activity of bare and Bi decorated THH Pd NCs was studied in alkaline medium at various temperatures Bi decorated THH Pd NCs exhibited 3 times enhancement in the activity for ethanol oxidation Activation energy for ethanol oxidation reduced significantly with an optimum Bi-decoration on THH Pd NCs Abstract: Tetrahexahedral Pd nanocrystals (THH Pd NCs) were prepared on a glassy carbon electrode using a programmed square-wave potential electrodeposition method, and modified by Bi adatoms with a range of coverages via the cyclic voltammetry method. The reactivity of the catalysts prepared towards ethanol electrooxidation reaction (EOR) was studied in alkaline medium at various temperatures and under other conditions that practical fuel cells operate. Significant activity enhancements were observed for the Bi-modified THH Pd NCs with an optimum Bi coverage (θBi ) of around 0.68 being obtained. Furthermore, it was found that increasing temperature from 25 °C to 60 °C enhances the reactivity significantly. The general kinetics data of EOR on Bi-decorated and bare THH Pd NCs have also been obtained, from the activation energy calculated based on Arrhenius plots, and compared. At the optimum Bi coverage, an enhancement in the activity of almost 3 times was achieved, and the corresponding activation energy was found to be reduced significantly.